An unusual case of foreign body aspiration - Vanitha Palanisamy; Sia Kian Joo; Chong Aun Wee; Mohd Afiq mohd Amin; Shahrul Amry Hashim; Ng Syiao Wei (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Tracheo-Oesophageal Puncture (TEP) with voice prosthesis insertion is considered as a gold standard among various voice rehabilitation procedures in laryngectomized patients. It is easily reversible with a high success rate, and the speech, which closely resembles laryngeal speech, develops faster than esophageal speech. However the prosthesis has to be cleaned regularly to ensure proper function as well as longevity of the voice prosthesis valve system. There are not many incidents of the voice prosthesis cleaning brush reported, as the cleaning brush is made to be durable and able to withstand repetitive usage. Hereby we describe an unusual case of a laryngectomized patient who had aspirated a broken tip of a cleaning brush while cleaning his voice prosthesis. The delay in removal of the aspirated foreign body due to technical difficulty had led to lung collapse subjecting the patient to partial lobectomy. We would like to highlight several aspects in this case report, firstly patients should be counselled regarding the proper techniques to clean the voice prosthesis and they should be vigilant during the cleaning process to prevent aspiration in case of accidental broken of cleaning brush. Secondly the incident should be reported to the manufacturer so that the durability of the cleaning brush is reviewed and improvised. Lastly, prompt management of foreign body aspiration should be implied to prevent complications.